2007
DOI: 10.1186/1748-717x-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative external beam radiotherapy and reduced dose brachytherapy for carcinoma of the cervix: survival and pathological response

Abstract: Purpose: To evaluate the pathologic response of cervical carcinoma to external beam radiotherapy (EBRT) and high dose rate brachytherapy (HDRB) and outcome. Materials and methods:Between 1992 and 2001, 67 patients with cervical carcinoma were submitted to preoperative radiotherapy. Sixty-five patients were stage IIb. Preoperative treatment included 45 Gy EBRT and 12 Gy HDRB. Patients were submitted to surgery after a mean time of 82 days. Lymphadenectomy was performed in 81% of patients. Eleven patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In certain institutions in more advanced stages (I/B2-II/B) the preoperative treatment is combined RT (tele+brachytherapy), with or without concomitant ChT, followed by adjuvant hysterectomy. The majority of these studies concluded that in patients with pCR obtained by preoperative BT the LTC and the OS was better than in cases that showed minimal or no regression to RT [4,5,7,19]. However, most of the studies that deal with the effect of preoperative RT are retrospective, with no control group, so there is no direct comparison between the results of surgery alone versus preoperative BT followed by surgery.…”
Section: Discussionmentioning
confidence: 90%
“…In certain institutions in more advanced stages (I/B2-II/B) the preoperative treatment is combined RT (tele+brachytherapy), with or without concomitant ChT, followed by adjuvant hysterectomy. The majority of these studies concluded that in patients with pCR obtained by preoperative BT the LTC and the OS was better than in cases that showed minimal or no regression to RT [4,5,7,19]. However, most of the studies that deal with the effect of preoperative RT are retrospective, with no control group, so there is no direct comparison between the results of surgery alone versus preoperative BT followed by surgery.…”
Section: Discussionmentioning
confidence: 90%
“…This may related to effect of radiotherapy to shrink the tumor mass that compress the ureter. 26 Our study did have certain limitations. The study population was retrospectively enrolled from a single center in Indonesia.…”
Section: Discussionmentioning
confidence: 87%
“…Definitive RT includes external beam radiation therapy (EBRT) to the pelvis and intracavitary brachytherapy (BT). RT in combination with surgery has been used for treatment of local disease, where RT has been added postoperatively to cases, showing unfavorable prognostic feature at surgery or has been given preoperatively [14]. Comparisons between treatment regimens with different fractionations, dose rates and treatment time as well as the evaluation of their effectiveness on tumor and normal tissues is possible through the use of bioeffect dose models that take into account the variation of the response with all the above-mentioned factors.…”
Section: Purposementioning
confidence: 99%